The Paradox of Pesantren Education in the Implementation of Islamic Law: Study of Pesantren Kyai Notion in Mojokerto - Ainul Yaqin; Rozi, Syaikhu; Sham, Fariza Md (Jurnal Pendidikan Islam, 2020)
The teaching of classical books (Kitab Kuning) is a tradition of pesantren education that has lasted a long time. The teaching aims so that students and Muslims can implement the teachings contained in classical books in everyday life. The purpose of this study is to reveal the paradoxical problems faced by santri and Muslims regarding the differences between the content of classical books and their daily application. This research focuses on pesantren Kyai in Mojokerto regarding this paradoxical problem, which is a determining factor in the style and variety of pesantren education management. This study used qualitative methods. Data were collected using interviews, observation, and documentation techniques. This study's results indicate that Kyai pesantren's notions in Mojokerto can be categorized in the textual-moderate category with the characteristics that they cannot accept the contextual interpretation of Islamic law and tend to be textual. However, this attitude does not encourage Kyai to impose Islamic law and does not force the form of an Islamic state. The education style that results from this notion is that pesantren education tends to be closed and does not accept religious values changes. However, it is open and accepts changes in general education by opening formal educational institutions. This study provides an overview of the style of pesantren education and the factors that influence it.